2020
DOI: 10.3390/cells9040902
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved LIR Motif in Connexins Mediates Ubiquitin-Independent Binding to LC3/GABARAP Proteins

Abstract: Gap junctions (GJ) are specialized cell-cell contacts formed by connexins (Cxs), which provide direct communication between adjacent cells. Cx43 ubiquitination has been suggested to induce the internalization of GJs, as well as the recruitment of the autophagy receptor p62 to mediate binding to LC3B and degradation by macroautophagy. In this report, we describe a functional LC3 interacting region (LIR), present in the amino terminal of most Cx protein family members, which can mediate the autophagy degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, we found that LY294002 decreased Cx43 protein levels. This effect may be associated with the fact that when autophagy is induced (such as during hunger), internalized Cx43 will be degraded by autophagy ( Catarino et al, 2020 ). Autophagy has been identified as an important pathway in the degradation of different types of Cxs, and autophagy induced by different factors will directly affect the expression level of Cxs ( Iyyathurai et al, 2016 ; D’hondt et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that LY294002 decreased Cx43 protein levels. This effect may be associated with the fact that when autophagy is induced (such as during hunger), internalized Cx43 will be degraded by autophagy ( Catarino et al, 2020 ). Autophagy has been identified as an important pathway in the degradation of different types of Cxs, and autophagy induced by different factors will directly affect the expression level of Cxs ( Iyyathurai et al, 2016 ; D’hondt et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that autophagy leads to the degradation of Cx43 during ischemia, [ 36 ] and gene silencing of autophagy-related genes leads to the accumulation of Cx43 and decreases the co-localization of LC3B and Cx43. [ 37 ] Relevant studies have also shown that during the middle part of M1-type macrophage polarization, autophagy is enhanced, leading to increased degradation of Cx43. [ 38 ] Our results showed that autophagy was increased at 48 hours which led to a decrease of Cx43 at 48 hours (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, unconventional secretion of cytosolic proteins could also take place to prevent PTMs that can inactivate them as seen in the case of unconventional secretion of FGF2 which prevents its O-glycosylation that makes it biologically inactive (Wegehingel et al, 2008). Similarly, in another example, it is reported that the conserved LIR motif in connexins mediate the ubiquitin independent binding to the autophagic proteins of LC3 (Catarino et al, 2020). Likewise, the specific phosphorylation of the small heat shock protein, α-Crystallin B at the Ser59 residue enhances autophagy mediated secretion (D'Agostino et al, 2019).…”
Section: Key Research Perspectivesmentioning
confidence: 99%